Rescue of Defective Electroretinographic Responses in Dp71-Null Mice With AAV-Mediated Reexpression of Dp71 - Barboni, Mirella Telles Salgueiro (Invest Ophthalmol Vis Sci, 2020)
PURPOSE: To study the potential effect of a gene therapy, designed to rescue the expression of dystrophin Dp71 in the retinas of Dp71-null mice, on retinal physiology. METHODS: We recorded electroretinograms (ERGs) in Dp71-null and wild-type littermate mice. In dark-adapted eyes, responses to flashes of several strengths were measured. In addition, flash responses on a 25-candela/square meters background were measured. On- and Off-mediated responses to sawtooth stimuli and responses to photopic sine-wave modulation (3–30 Hz) were also recorded. After establishing the ERG phenotype, the ShH10-GFP adeno-associated virus (AAV), which has been previously shown to target specifically Müller glial cells (MGCs), was delivered intravitreously with or without (sham therapy) the Dp71 coding sequence under control of a CBA promoter. ERG recordings were repeated three months after treatment. Real-time quantitative PCR and Western blotting analyses were performed in order to quantify Dp71 expression in the retinas. RESULTS: Dp71-null mice displayed reduced b-waves in dark- and light-adapted flash ERGs and smaller response amplitudes to photopic rapid-on sawtooth modulation and to sine-wave stimuli. Three months after intravitreal injections of the ShH10-GFP-2A-Dp71 AAV vector, ERG responses were completely recovered in treated eyes of Dp71-null mice. The functional rescue was associated with an overexpression of Dp71 in treated retinas. CONCLUSIONS: The present results show successful functional recovery accompanying the reexpression of Dp71. In addition, this experimental model sheds light on MGCs influencing ERG components, since previous reports showed that aquaporin 4 and Kir4.1 channels were mislocated in MGCs of Dp71-null mice, while their distribution could be normalized following intravitreal delivery of the same ShH10-GFP-2A-Dp71 vector.